Incidence and prevalence, and medication use among adults living with dermatomyositis: an Alberta, Canada population-based cohort study - Mohammed Osman; Karen J. B. Martins; Kai On Wong; Khanh Vu; Alexis Guigue; Jan Willem Cohen Tervaert; Robert Gniadecki; Scott W. Klarenbach (Scientific Reports, 2023)
Abstract Dermatomyositis is a rare disease characterized by progressive muscle weakness and skin rashes. Estimates of incidence and prevalence are fundamental measures in epidemiology, but few studies have been conducted on dermatomyositis. To address this knowledge gap, we conducted a population-based study to determine the contemporary incidence (between 2013 and 2019) and prevalence (2019) of adults living with dermatomyositis using administrative health data in Alberta, Canada. We also described disease-related medication use, as there are very few approved medications for the treatment of dermatomyositis, and no Canadian therapeutic guidelines. The average age- and sex-standardized annual incidence of dermatomyositis was 2.8–3.0 cases per 100,000 adults, and prevalence was 28.6 cases per 100,000 adults, which is greater than reported in other cohorts. Dermatomyositis-related medication use decreased from 73% in the first year to 46% in the eighth year after diagnosis. Glucocorticoids were the most commonly used drug class, often taken concurrently with various immunomodulatory agents; this medication use aligns with empirically-based recommendations and the few therapeutic guidelines for dermatomyositis. Considering that Alberta may have one of the highest rates of dermatomyositis among adults, further research on the burden of disease is warranted for planning within the health care system.